2015
DOI: 10.1093/femspd/ftv065
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic potential ofEscherichia coliclinical strains from orthopedic implant infections towards human osteoblastic cells

Abstract: Escherichia coli is one of the first causes of Gram-negative orthopedic implant infections (OII), but little is known about the pathogenicity of this species in such infections that are increasing due to the ageing of the population. We report how this pathogen interacts with human osteoblastic MG-63 cells in vitro, by comparing 20 OII E. coli strains to two Staphylococcus aureus and two Pseudomonas aeruginosa strains. LDH release assay revealed that 6/20 (30%) OII E. coli induced MG-63 cell lysis whereas none… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 45 publications
(68 reference statements)
4
33
0
Order By: Relevance
“…The microbiological results from the in vivo study revealed that moxifloxacin-loaded sol-gel showed an all-or-nothing response when used to coat the implant and S. aureus or E. coli infection is induced (Figure 11) as expected. The femoral deformation observed in S. aureusinfected groups with non-coated implants is consistent with the ability of S. aureus to internalize in osteoblasts (Cremet et al, 2015) and cause deforming osteomyelitis in chronic bone infections (de Mesy Bentley et al, 2017) (Figure 10). In the case of E. coli, the bone deformation observed in infected groups FIGURE 13 | Immunohistochemistry for markers of different bone cells.…”
Section: Discussionsupporting
confidence: 72%
“…The microbiological results from the in vivo study revealed that moxifloxacin-loaded sol-gel showed an all-or-nothing response when used to coat the implant and S. aureus or E. coli infection is induced (Figure 11) as expected. The femoral deformation observed in S. aureusinfected groups with non-coated implants is consistent with the ability of S. aureus to internalize in osteoblasts (Cremet et al, 2015) and cause deforming osteomyelitis in chronic bone infections (de Mesy Bentley et al, 2017) (Figure 10). In the case of E. coli, the bone deformation observed in infected groups FIGURE 13 | Immunohistochemistry for markers of different bone cells.…”
Section: Discussionsupporting
confidence: 72%
“…Bacterial internalization experiments were adapted from Crémet et al . study 28 . Briefly, the MG-63 monolayers were infected for 2 h (multiplicity of infection (MOI) of 100:1).…”
Section: Methodsmentioning
confidence: 99%
“…More work should be done to circumvent this type of detector’s bottlenecks, some of which include inhomogeneous spatial resolution, limited imaging depth, and acoustic mismatches especially for the human skull [39, 47]. PACT with a high frame rate, tunable laser sources, a well-designed acoustic array and a corresponding reconstruction algorithm are necessary to attract more clinical attention.…”
Section: Specific Embodiments Of Paimentioning
confidence: 99%